2010
DOI: 10.1007/s11084-010-9211-4
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence and Evolution of Life in a “Fatty Acid World” Based on Quantum Mechanics

Abstract: Quantum mechanical based electron correlation interactions among molecules are the source of the weak hydrogen and Van der Waals bonds that are critical to the self-assembly of artificial fatty acid micelles. Life on Earth or elsewhere could have emerged in the form of self-reproducing photoactive fatty acid micelles, which gradually evolved into nucleotide-containing micelles due to the enhanced ability of nucleotide-coupled sensitizer molecules to absorb visible light. Comparison of the calculated absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…This behavior again matches what is experimentally seen for such interactions [2,3], namely a shifting of the lowest energy Vis spectrum excited states of complex quantum systems, due to covalent and Van der Waals bonding interactions with the additional molecules. This is also consistent with our general finding that the inclusion of more molecules in the photosynthetic systems of artificial minimal cells resulted in longer wavelengths for the absorption spectrum [5][6][7][8]. The shift of the absorption spectrum to the red for the artificial protocell photosynthetic centers might be considered as the measure of the complexity of these systems.…”
Section: Quantum Investigations Of [Ru(bpy) 2 (4-4'-me 2 -22'-bpy)]supporting
confidence: 91%
See 2 more Smart Citations
“…This behavior again matches what is experimentally seen for such interactions [2,3], namely a shifting of the lowest energy Vis spectrum excited states of complex quantum systems, due to covalent and Van der Waals bonding interactions with the additional molecules. This is also consistent with our general finding that the inclusion of more molecules in the photosynthetic systems of artificial minimal cells resulted in longer wavelengths for the absorption spectrum [5][6][7][8]. The shift of the absorption spectrum to the red for the artificial protocell photosynthetic centers might be considered as the measure of the complexity of these systems.…”
Section: Quantum Investigations Of [Ru(bpy) 2 (4-4'-me 2 -22'-bpy)]supporting
confidence: 91%
“…This implies that the covalent bonding of the 8-oxo-guanine to the PNA fragment to one of the bipyridines breaks the D 3 symmetry and splits the degenerate lines at 455.2 nm, 450.7 nm, 441.6 nm, and 429.7 nm (see Table 2). Despite the greater complexity of the larger covalently bonded 8-oxo-guanine-PNA-Ru(bpy) 2+ 3 supermolecule compared with that of the Ru(bpy) 2+ 3 molecule alone, the peaks of the spectrum of the more complex molecule did not show a clear shift to the red as had been previously seen for the softly "bonded" supramolecule based on the 1,4-bis(N,Ndimethylamino) naphthalene sensitizer molecule to which the other molecules are loosely attached by hydrogen bonds and Van der Waals forces [6][7][8]13]. …”
Section: Quantum Modellingsupporting
confidence: 54%
See 1 more Smart Citation
“…For example, Erwin Schrödinger in his 1944 book "What is life" predicted some of the basic characteristics of DNA before it had been discovered [14]. More recently, it has been suggested that quantum effects would have been selected for at the beginnings of life due to their ability to improve efficiency -in particular, quantum tunnelling and superposition [29,30]. Indeed, the concept of directed "quantum evolution" has been proposed, which could explain how the first "self-replicator" molecules arose using basic quantum principles and gets around the problem of how, given the enormous degrees of freedom even a relatively short 15-20 unit peptide or nucleic acid displays, could have arisen [31].…”
Section: The Emergence Of Quantum Biologymentioning
confidence: 99%
“…There are many hypotheses for the origin of bacteria-ranging from astrophysical bases of Universe (Ehrenfreund et al, 2002) and self-reproducing coacervates (Oparin, 1973;Colgate et al, 2003;Vasas et al, 2012) to the first mitotic cells (Sagan, 1967;Ratcliff et al, 2012;Montagnes et al, 2012). Recently, the quantummechanical effects (Patte, 1967;Pati, 2004;Davies, 2008;Tamulis and Grigalavicus, 2010;Fleming et al, 2011) and the anthropic principles that implies that Universe must be consistent with the existence of life (Carr and Rees, 1979;Hoyle and Wickramasinghe, 1999;Vidal, 2010;Kamenshchik and Teryaev, 2013) need to be extended into the understanding of life. In the present approach we developed the hypothesis for possible physical determination of the mass, size, doubling time and density parameters of the unicellular organisms on the Earth.…”
Section: Introductionmentioning
confidence: 99%